TANTANGAN GURU DALAM MENGADAPTASI MEDIA PEMBELAJARAN DIGITAL DI SDIT SWASTA: STUDI KASUS MULTI-SITUS DI KOTA PEKANBARU - Nabiha; Heldanita; Aramudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the demands of technological adaptation in Islamic elementary schools, which frequently encounter operational constraints, limited infrastructure, and teacher workload challenges in aligning multimedia content. The primary objective of this study is to analyze teachers' adaptation challenges in integrating digital learning media. The method employed is a qualitative multi-site case study approach across three private SDITs in Pekanbaru using purposive sampling. The results indicate that teachers' challenges are no longer merely technical-operational, but rather an intersection of cognitive-pedagogical workloads in lesson planning, school internet disparities, and the necessity of Islamic value curation. Although digital media is proven to enhance student focus , teachers feel burdened by intensive preparation time. The conclusion of this study emphasizes that successfully addressing teacher challenges in adapting digital learning media in private SDITs heavily relies on systemic synergy between competency readiness, managerial infrastructure support, and standardized content filtering.